Method, device and equipment for calculating engineering quantity of laying cable trench and storage medium - LIANG MINXIN; CUI WEI; LIU FULAI (2022)
The invention relates to a cable trench laying engineering quantity calculation method, device and equipment and a storage medium. The method comprises the steps of receiving a first operation of a user; the first operation is used for determining the style of the cable trench and the starting point position and the final point position of the cable trench; according to the style of the cable trench and the starting point position and the ending point position of the cable trench, generating a foundation slab primitive of the cable trench; establishing a three-dimensional model of the cable trench according to the basic bottom plate primitive of the cable trench; According to the three-dimensional model of the cable trench, calculating the engineering quantity of laying the cable trench. The method can efficiently calculate the engineering quantity of laying the cable trench. 本申请涉及一种铺设电缆沟的工程量计算方法、装置、设备及存储介质。该方法包括：接收用户的第一操作；所述第一操作用于确定电缆沟的样式以及所述电缆沟的起点位置和终点位置；根据所述电缆沟的样式以及所述电缆沟的起点位置和终点位置，生成所述电缆沟的基础底板图元；根据所述电缆沟的基础